The Effect of Dismenorerage Exercise on Dysmenorerage in Adolescent Women in Bah Jambi Private Junior High School - Saputri, Ika Nur; Pasaribu, Yoma Yopa Ate Malem (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
Dysmenorrhea is pain during menstruation that is felt in the lower abdomen and also in muscle pain in the upper thighs, lower back, pelvis, and waist to calves. Dysmenorrhea also affects emotions and anxiety due to feelings that are uncomfortable and foreign to adolescents. Therefore dysmenorrhea must be handled so that these impacts can be minimized. Every year, dysmenorrhea is a problem that always arises among women of childbearing age. This research was conducted because there was data from a preliminary study and it was found that 90% of young women experienced dysmenorrhea, namely in young women at Bah Jambi Private Middle School. The purpose of this study was to determine the effect of dysmenorrhea exercise on menstrual pain (dysmenorrhea) in young women at Bah Jambi Private Middle School. Quasi-experimental research with a one-group pre-test post-test design scheme. A total of 37 young women were selected to be the sample, which was determined by purposive sampling. The resulting data in the form of a search scale will be analyzed using the Wilcoxon Sign Rank Test. The pain scale before the dysmenorrhea exercise showed that most of the respondents experienced menstrual pain that interfered with their activities. After doing the exercise, the menstrual pain for young women becomes a little painful. Based on the Wilcoxon Sign Rank Test with a 95% level of confidence, the value of p = 0.00 is obtained, where this value is less than 0.05, which means that the alternative hypothesis is accepted. So it can be concluded that dysmenorrhea exercise affects reducing menstrual pain in young women at Bah Jambi Private Middle School.